High early post-operative complication rate after elective aseptic orthopedic implant removal of upper and lower limb - Höppchen, Arnold; Heilgeist, Eva; Tinelli, Marco; Bischel, Oliver E. (Journal of orthopaedic research, 2018)
The necessity of orthopedic implant removal is under intense discussion and even if it is performed as an elective procedure, the risk of complications is present. Aim of the study was to identify parameters responsible for an increased risk of early post-operative complications after elective aseptic orthopedic implant removal. We reviewed 1,545 cases of aseptic and elective orthopedic implant removal between 2009 and 2011. The patient́s demographic data, time and duration of operation, patient́s comorbidities, and presence of complications in the first 4 weeks after implant removal were evaluated. Patients with signs of infection at the time of the surgical procedure were excluded from this study. 579 women and 966 men who underwent elective aseptic orthopedic implant removal were identified. Mean age at implant removal was 42 years and mean duration of the surgical procedure was 37 min. In this cohort, 70 patients (4.5%) underwent elective aseptic implant removal after 6pm. 52 patients (3.37%) operated on during daytime suffered from complications post-operatively and five patients (0.3%) who were operated on during the night experienced complications. The parameters age, sex, BMI, and surgeon showed no statistically significant differences for the risk of post-operative complications. Patients’ comorbidities such as diabetes seem to have influence but were not statistically significant either. Patients with revision surgery since their first operation, nocturnal surgery and longer duration of the procedure showed a statistically significant higher risk for complications, especially in the lower leg. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1035-1039, 2018.